2007
DOI: 10.1094/mpmi-20-4-0392
|View full text |Cite
|
Sign up to set email alerts
|

A Polygalacturonase-Inhibiting Protein from Grapevine Reduces the Symptoms of the Endopolygalacturonase BcPG2 from Botrytis cinerea in Nicotiana benthamiana Leaves Without Any Evidence for In Vitro Interaction

Abstract: Six endopolygalacturonases from Botrytis cinerea (BcPG1 to BcPG6) as well as mutated forms of BcPG1 and BcPG2 were expressed transiently in leaves of Nicotiana benthamiana using agroinfiltration. Expression of BcPG1, BcPG2, BcPG4, BcPG5, and mutant BcPG1-D203A caused symptoms, whereas BcPG3, BcPG6, and mutant BcPG2-D192A caused no symptoms. Expression of BcPG2 caused the most severe symptoms, including wilting and necrosis. BcPG2 previously has been shown to be essential for B. cinerea virulence. The in vivo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…We previously showed that PGs from B. cinerea are able to induce necrosis in tomato, broad bean, and N. benthamiana (Kars et al, 2005;Joubert et al, 2007). This response required enzyme activity, and there were marked differences in necrosisinducing activities between individual PGs, with BcPG2 causing massive and rapid tissue collapse (less than 30 min in broad bean) and BcPG3 causing no detectable symptoms in any of the three plants mentioned (Kars et al, 2005;Joubert et al, 2007). The response in Arabidopsis to PGs, therefore, appears to be fundamentally different from that in tomato, broad bean, and N. benthamiana.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that PGs from B. cinerea are able to induce necrosis in tomato, broad bean, and N. benthamiana (Kars et al, 2005;Joubert et al, 2007). This response required enzyme activity, and there were marked differences in necrosisinducing activities between individual PGs, with BcPG2 causing massive and rapid tissue collapse (less than 30 min in broad bean) and BcPG3 causing no detectable symptoms in any of the three plants mentioned (Kars et al, 2005;Joubert et al, 2007). The response in Arabidopsis to PGs, therefore, appears to be fundamentally different from that in tomato, broad bean, and N. benthamiana.…”
Section: Discussionmentioning
confidence: 99%
“…For transient expression in Nicotiana benthamiana, Bcpg3 with a plant PR1 signal peptide was amplified from pAT2-3 (Joubert et al, 2007) with primers AT265/AT268 and cloned into donor vector pDONR207 to obtain the entry vector, which was checked by sequencing. Expression vectors were created by Gateway cloning into pSOL2095 or pGWB20 (Nakagawa et al, 2007) with the corresponding entry vectors and transformed into A. tumefaciens C58C1, carrying helper plasmid pCH32 , or into A. tumefaciens GV3101 (only for SERK2 and BAK1 constructs).…”
Section: Plasmid Construction and Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while evolutionary analyses were made on PGIPs of different plant families, only one particular PGIP (PvPGIP2) was mutagenized and its inhibitory capability tested against a limited number of fungal PGs. Furthermore, because the in vitro assay conditions are unlikely to mimic the physiological microenvironment of the apoplast and the interaction between the variants and PGs might differ in planta from that detected in vitro (49), the effects of the variants obtained in this work on plant response against pathogens therefore cannot be easily predicted and remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…To counteract the activity of fungal pectinases, many plants express polygalacturonase-inhibiting proteins and PME inhibitors, which are localized in the cell wall. The role of these proteins in plant defense against B. cinerea has been extensively demonstrated (Powell et al, 2000;Ferrari et al, 2003;Sicilia et al, 2005;Joubert et al, 2006Joubert et al, , 2007Lionetti et al, 2007). The interaction with the inhibitors not only limits the destructive potential of polygalacturonases but also leads to the accumulation of elicitoractive OGAs (De Lorenzo and Ferrari, 2002).…”
mentioning
confidence: 99%